The Development of Teacher Efforts to Improve The Mathematical Reasoning Abilities Through The Problem Based Learning - Rahmah, Siti; Johar, Rahmah; Saminan, Saminan (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study is to determine teacher efforts to improve students' mathematical reasoning abilities through the Problem Based Learning model. This research is a classroom action research consisting of two cycles, namely planning, implementation, observation, and reflection. The research subjects were 28 students of class VII-1 SMP Negeri 2 Siantan, Anambas Islands Regency. The research instrument used was the teacher's observation sheet and the mathematical reasoning ability test. Data collection is done through observation and tests. The data obtained were analyzed qualitatively and described in a descriptive form. The results obtained are the mathematical reasoning ability of students in the first cycle of 2.27 and the second cycle of 2.83. Based on the results of the study showed that the efforts of teachers made in the second cycle were better than the first cycle, so that an increase in students' mathematical reasoning abilities in the second cycle was in the good category.